RISK FACTORS FOR REGIONAL LYMPH NODE METASTASIS IN PAPILARY THYROID CARCINOMA - Viator Nadeak; Raden Yohana; Kiki Rizki (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
Abstract Thyroid cancer is a common malignancy of the endocrine system. One of the current challenges is to control the loco-regional recurrence. Until today, clinical characteristics and histopathological result as predictive factors that can be used to identify patients for prophylactic radical neck dissection are still unclear. Therefore this study aimed to assess the relationship between clinical characteristics and histhopatological result to regional neck lymph node metastases. This was a cross-sectional study, to explain the relationship between clinical characteristic and histopathological result in the incidence of regional neck lymph node metastases. During the study period January 2017 to January 2018, there were 74 patients included in the analysis. The mean age of the patient was 45.31 ± 13,433 years. There were 47 (63.3%) patients with the age categories of <20 and> 40 years old and 27 (36.5%) with age category 20-40 years old. Male patients was accounted for 15 (20.3%) and women 59 (79.7%). The size categories of the tumor were <= 5cm 67 (90.5%) and > 5 cm 7 (9.5%). There were 57 (77.0%) patients with papilary thyroid carcinoma (PTC) and 17 (23.0%) with follicular thyroid carcinoma (FTC). There were 30 (40.5%) positive and 44 (59.5%) negative for Lymphovascular Invasion, For Capsular invasion there were positive 27 (36.5%) and negative 47 (63.5%). There were 45 (60.8%) and 29 (39.2%) patients with positive and negative regional neck lymph node metastases. The factors that influence the occurrence of lymph metastasis were sex, lymphovascular invasion, capsular invasion and histopathology of papillary thyroid carcinoma. Keywords : Local Recurrence, Lymph Node Metastases, Papilary Thyroid, Risk Factors Carcinoma, Thyroid Carcinoma.